Analysis of the Influence of Spices on the Yu-Shiang Sauce Flavors Based on E-nose and GC-IMS Technology - Hao ZHANG; Tianlong GAO; Yuwen YI; Xuemei CAI; Jing DENG; Yingming TANG; Siyuan GU; Mingfeng QIAO (Shipin gongye ke-ji)
To identify the effects of spices on the flavor formation of Yu-Shiang sauce, this study conducted a previously unexplored experiment examining the impacts of ginger, scallions, garlic, and pickled chili on flavor, quantitative descriptive analysis (QDA), gas chromatography-ion mobility spectroscopy (GC-IMS) technology, and electronic nose (E-nose) were used to analyze the compound changes. The results of sensory analysis and the electronic nose test showed that the deletion scallions disrupted the balance of fish flavor and had the greatest impact on flavor. Deletion pickled chili peppers reduced the spiciness and freshness, had effect on the flavor, but the overall similarity remained high. The lack of ginger had the least impact on the balanced flavor presentation. Deletion garlic had an enhancing effect on saltiness. GC-IMS result showed that 91 kinds of volatile compounds, including 26 kinds of aldehydes, 18 kinds of alcohols, 13 kinds of ketones, 8 kinds of esters, 8 kinds of alkanes, 5 kinds of sulphur-containing compounds, 2 kinds of ethers, 1 kind of acid, 10 kinds of heterocyclic compounds. The study found that the alkanes of the sample group with missing scallions decreased from 11.06% to 5.41% in the reference group, indicating that the missing scallions had the greatest impact on fish flavor. The aldehydes of sample group with missing pickled chili increased from 19.89% to 26.12% and alcohols significantly increased from 9.41% to 15.06%. This research was concluded that the lipid flavor came from aldehydes and alcohols was the main factor affected the flavor of Yu-Shiang sauce. The research results provide theoretical basis and guidance for the industrial development of Yu-Shiang sauce